Introdução a noções de cálculo diferencial e integral no ensino médio no contexto das TIC: implicações para prática do professor que ensina matemática - Farias, Maria Margarete do Rosário [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The difficulties related to the processes of teaching and learning Differential and Integral Calculus (DIC) are very old and the focus of concern of teachers and researchers in the field of mathematics education. With the evolution of technology, we notice that when used well, these can promote learning, when we consider aspects such as geometric visualization, the dynamic nature of exploration and the opportunities to consider the properties of mathematical objects. In this research study, debates around Information and Communication Technologies (ICT) created opportunities for all participants to consider the possibilities and challenges associated with the introduction of ICT in the secondary school. With the advances in technologies, new educational software allows teachers to consider new theoretical-methodological approaches for the teaching of concepts taught in their classes. Today it is feasible that concepts of ICT, that have always been dynamic in nature, can be approached dynamically as well, using software such as GeoGebra or Winplot. With this consideration, in this study we propose to answer the following question: What are the implications, for a mathematics teacher's practices, of using ICTs to introduce concepts of Differential and Integral Calculus when teaching functions in the secondary school? The goal of this thesis is to determine secondary mathematics teachers' reconceptualization of their practice as they introduce notions of Differential and Integral Calculus in their teaching of functions using ICTs. The theoretical framework of the study is based on the interrelations of Activity Theory (AT) and Communities of Practice (CoP). The methodological approach was qualitative, using participant observation; and methodological instruments consisted of an online extension course for and interviews with secondary mathematics teachers - subjects of the research study. Data analyses were based on the ideas of...

As dificuldades relacionadas aos processos de ensinar e aprender Cálculo Diferencial e Integral (CDI) são bastante antigas e alvo da preocupação de professores e pesquisadores do campo da Educação Matemática. Com a evolução da tecnologia, percebemos que, quando bem utilizada, promove ganhos, colocando em destaque aspectos como a visualização geométrica, a dinamicidade do software e a apreensão de propriedades de objetos matemáticos. Neste trabalho de pesquisa, o debate sobre as Tecnologias da Informação e Comunicação (TIC) oportuniza a todos os envolvidos refletirem sobre as possibilidades e entraves associados à prática docente quanto à perspectiva de introduzir noções de CDI I no Ensino Médio. Nessa conjuntura, compreendemos, portanto, que, conforme avança a tecnologia, os software educativos que têm sido desenvolvidos possibilita aos professores considerar novas abordagens teórico-metodológicas no ensino de conceitos trabalhados em sala de aula. Hoje é possível que conceitos do CDI, que sempre foram de natureza dinâmica, possam ser abordados de modo também dinâmico, por meio de software, como o GeoGebra e o Winplot. Com base nisso, propomos nesta pesquisa responder o seguinte questionamento: quais são as possíveis implicações da prática do professor de Matemática quando inter-relaciona noções de Cálculo Diferencial e Integral ao ensinar Funções no Ensino Médio, mediante utilização das TIC? O objetivo da Tese consiste em evidenciar as implicações para a prática do professor que ensina Matemática, quando inter-relaciona noções de Cálculo Diferencial e Integral ao ensinar Funções no Ensino Médio, utilizando as TIC. O aporte teórico da pesquisa baseia-se nas inter-relações de conceitos da Teoria da Atividade (TA), e de conceitos de Comunidades de Práticas (CoP). A metodologia adotada consiste em uma abordagem qualitativa, mediante a observação participante; tomando como instrumentos...
Keywords: Matemática - Estudo e ensino; Tecnologias de informação e comunicação; Pratica de ensino; Cálculo diferencial; Calculo integral; Ensino médio